2022
DOI: 10.3390/ijms23042334
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi Anemia Patients from an Indigenous Community in Mexico Carry a New Founder Pathogenic Variant in FANCG

Abstract: Fanconi anemia (FA) is a rare genetic disorder caused by pathogenic variants (PV) in at least 22 genes, which cooperate in the Fanconi anemia/Breast Cancer (FA/BRCA) pathway to maintain genome stability. PV in FANCA, FANCC, and FANCG account for most cases (~90%). This study evaluated the chromosomal, molecular, and physical phenotypic findings of a novel founder FANCG PV, identified in three patients with FA from the Mixe community of Oaxaca, Mexico. All patients presented chromosomal instability and a homozy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Published information on cohorts of patients with IBMFS from LMICs, including Mexico, remains scarce. Comprehensive available data of Mexican patients with IBMFS are predominantly case reports or small case series, such as those for patients with FA ( García-de Teresa et al, 2019 ; Reyes et al, 2022 ), or case reports from a limited number of patients with DC or SCN ( López-Rodríguez et al, 2022 ; Picos-Cárdenas et al, 2022 ; Velez-Tirado et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published information on cohorts of patients with IBMFS from LMICs, including Mexico, remains scarce. Comprehensive available data of Mexican patients with IBMFS are predominantly case reports or small case series, such as those for patients with FA ( García-de Teresa et al, 2019 ; Reyes et al, 2022 ), or case reports from a limited number of patients with DC or SCN ( López-Rodríguez et al, 2022 ; Picos-Cárdenas et al, 2022 ; Velez-Tirado et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the prevalence and phenotypic spectrum of IBMFSs in the Mexican population, and available studies concentrate on FA ( García-de Teresa et al, 2019 ; Reyes et al, 2022 ). To address current genotyping limitations, we implemented a clinical approach to expedite clinical suspicion and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent prospective study published that vertebrae anomalies are found in almost 50% of patients after intentional evaluation ( 245 ), which is in sharp contrast with the 4% described in the literature ( 37 , 133 ). Some reports have depicted less frequent anomalies, such as rib hypoplasia, Sprengel deformity, and hip dysplasia ( 149 , 225 , 261 264 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 99%